How I manage patients with Wiskott Aldrich syndrome. (12th March 2019) - Rivers, Elizabeth; Worth, Austen; Thrasher, Adrian J.; Burns, Siobhan O.
Summary: Wiskott Aldrich syndrome (WAS) is a primary immunodeficiency disease resulting in recurrent infections, eczema and microthrombocytopaenia. In its classical form, significant combined immune deficiency, autoimmune complications and risk of haematological malignancy necessitate early correction with stem cell transplantation or gene therapy. A milder form, X‐linked thrombocytopaenia (XLT), shares similar bleeding risk from thrombocytopaenia but is not associated with other significant clinical features and is generally managed conservatively. Here, we detail our approach to the diagnosis and treatment of classical WAS and XLT.